Keefektifan Bimbingan Kelompok Teknik Problem Solving untuk Meningkatkan Kebiasaan Belajar Siswa SMPN 8 Denpasar - Baiq Isna Maulida Famuji; Putu Agus Semara Putra Giri (Pusat Riset dan Inovasi Nasional, 2024)
Study habits are an important thing to pay attention to because they are one of the main components that support student achievement or learning success. However, quite a few students have poor study habits. This is reflected in the behavior of students who rarely do assignments, are not active in learning activities, do not prepare lesson materials and other behavior that indicates negative study habits. The main aim of this research is to improve the study habits of students at SMPN 8 Denpasar through a problem solving technique group guidance approach. The type of research used is quantitative research with experimental methods. The design used is one-group pretest-posttest. The instruments used are experimental guidelines prepared by researchers and tested by experts and the study habit scale used is adopted by Nawawi (2016). Subject determination uses purposive sampling. The subjects used in this research were eight students who had low study habit scores after a pretest with the study habit scale. The data analysis used is descriptive and inferential analysis in the form of the N-gain Score test and the Wilcoxon test. Based on the results of the pretest and posttest tables, there was an increase in students' study habits scores after being given the intervention, and based on the results of calculations using the SPSS Wilcoxon signed rank test. From this value it is known that 0.012 < 0.05 which means Ha is accepted. Based on the results of this analysis, it can be concluded that group guidance on problem solving techniques is effective in improving students' learning habits.